Lietuvos istorikas Jurgis Orda - Jegelevičius, Sigitas (Lietuvos istorijos studijos, 1997)
The report presents Jerzy Orda (1905.03.20–1972.06.06), a Lithuanian historian, Polish by origin, who wrote in Polish and Russian. He was well known both as an expert in the history of the Grand Duchy of Lithuania, the history and architecture of Vilnius, and a Lithuanian archivist and archeographer. Scientific circles, however, did not know that Jerzy Orda had contributed much to the historiography of Lithuania’s history, since his historiographical study, „Sources of Lithuania History Until 1795" (1949), has not yet been published. This study is considered to be the first historiographical review after the Second World War and has many features of the survey of written historical sources. It gives his point of view on the historiography of history as well. The study resembles the historiographical attitude of a well-known Russian historiographer, Vladimir Ikonnikov. The report investigated the study of Jerzy Orda being of great importance to Lithuanian historiography, as well as his short historiographical manuscript „Vilnius’ Central Archive of Manuscripts" (1948). The report also deals with Jerzy Orda’s unquestionable contribution to Lithuania’s history concerning Trakai and the castle history. The short article „Trakai Peninsula Castle" was published in 1960. It can be considered a solution to a very important problem related to the historiography of Lithuanian history.